Recent progress in hormone research : proceedings of the Laurentian Hormone Conference. - Pincus, Gregory, 1903-1967 (Academic Press Inc, Publishers, 1948)
Recent Progress in Hormone Research: Volume II is a collection of papers presented at the proceedings of the 1946 Laurentian Hormone Conference, held in St. Adele-on-High. This volume is organized into five parts encompassing 14 chapters that explore the methods of hormone analysis, the pituitary and metabolic hormones, and the clinical aspects of endocrinology. The first part discusses some applications of both ultraviolet and infrared absorption spectroscopy to the problem of the elucidation of the structure of sterol compounds. The subsequent parts cover the humoral or nervous factors, whic.